How does electronic word of mouth on Instagram affect travel behaviour in Indonesia: A perspective of the information adoption model - Pantas H. Silaban; Wen-Kuo Chen; Surmida Sormin; Yehezkiel Natamatua B. P. Panjaitan; Andri Dayarana K. Silalahi (Cogent Social Sciences)
Today, electronic word-of-mouth (eWOM) is considered one of tourism businesses’ most effective forms of communication. Using eWOM on social media as an alternative decision aid can benefit consumers. This study examines the information adoption model to determine how consumers adopt eWOM on Instagram, and the subsequent influence on their travel behaviour. This study identifies the need for information as a predictor of information usefulness, converted to adoption and visit intentions. To test the research hypotheses, 263 respondents who had visited destinations based on eWOM recommendations on Instagram participated in the experiment. The data were analysed using a structural equation modelling approach using Smart-PLS 3.0. The findings indicate that the need for information is the most significant factor affecting the usefulness of the information. Furthermore, source credibility and argument quality are critical factors in enhancing the information’s usefulness. Thus, this study has significantly contributed to the theory by adding the need of information to predict visit intentions in the IAM model. Consumers are more likely to adopt high-quality information and convert it into a visit intention. This study provides practical guidelines for tourism managers who wish to utilise social media platforms (e.g., Instagram) as marketing communication tools to encourage eWOM about their destinations.